2013
DOI: 10.1186/1471-2334-13-258
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-associated methicillin-resistant Staphylococcus aureus responsible for human colonization and infection in an area of Italy with high density of pig farming

Abstract: BackgroundLivestock-Associated MRSA (LA-MRSA) belonging to ST398 lineage, common among pigs and other animals, emerged in Central and Northern Europe, becoming a new risk factor for MRSA among farm workers. Strains belonging to ST398 can be responsible for human colonization and infection, mainly in areas with high livestock-farming. The aim of this study was to investigate the occurrence of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) human colonization and infections in an area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 36 publications
1
63
2
2
Order By: Relevance
“…The study showed that the MRSA prevalence among livestock was 13.8% (pigs: 25.8%, poultry: 9.3% and cattle: 6.2%) which is lower when compared with European countries, where the percentage in Germany and Netherlands was >35% 22,23 and in Poland 20.6%. 24 However, some Asian countries exhibit lower carriage of MRSA in livestock as is the case in China: 11.4%, 25 Korea: 3.2%, 22 Malaysia: 1.4%, 24 Japan: 0.9%, 29 and Taiwan: 14.4%. 26 In our study, MRSA carriage among livestock farmers was 15.9% (piggery: 25.8% poultry: 12.5% and cattle: 9.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that the MRSA prevalence among livestock was 13.8% (pigs: 25.8%, poultry: 9.3% and cattle: 6.2%) which is lower when compared with European countries, where the percentage in Germany and Netherlands was >35% 22,23 and in Poland 20.6%. 24 However, some Asian countries exhibit lower carriage of MRSA in livestock as is the case in China: 11.4%, 25 Korea: 3.2%, 22 Malaysia: 1.4%, 24 Japan: 0.9%, 29 and Taiwan: 14.4%. 26 In our study, MRSA carriage among livestock farmers was 15.9% (piggery: 25.8% poultry: 12.5% and cattle: 9.6%).…”
Section: Discussionmentioning
confidence: 99%
“…13 Similar to livestock, the livestock farmer's MRSA carriage also showed low prevalence compared to Europe and the USA. [21][22][23][24][25][26] But the Sri Lankan prevalence is higher than that of other Asian countries, which report …”
Section: Discussionmentioning
confidence: 99%
“…Farmers are confronted with two different consequences of this problem: the potential danger of animal colonization with drug-resistant bacteria for (i) humans living on or in the vicinity of farms (11)(12)(13) and for (ii) consumers of animal products (14)(15)(16)(17)(18). Indeed, livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) have been found in humans living and working in close contact with pigs and also in hospitals in rural areas (11,(19)(20)(21)(22)(23)(24)(25). In contrast, ESBL-E could possibly be transferred from animals to humans via meat products (16,(26)(27)(28).…”
mentioning
confidence: 99%
“…Molecular characterization revealed that the isolated clones are grouped in the complex 398 (CC398), called livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA). LA-MRSA has been shown with pathogenic to humans and can cause serious infections such as endocarditis and pneumonia (REISCHL et al, 2009;MONACO et al, 2013).…”
Section: Methicillin-resistant Staphylococcus (Mrs)mentioning
confidence: 99%